Introduction and characterization of charged functional domains into an esterified pectic homogalacturonan by a citrus pectin methylesterase and comparison of its modes of action to other pectin methylesterase isozymes. (August 2017) - Kim, Yang; Williams, Martin A.K.; Luzio, Gary A.; Cameron, Randall G.
Abstract: One of the four pectin methylesterase types isolated from Citrus sinensis var. Valencia fruit was used to demethylesterify a model homogalacturonan (HG) to 30%, 50% and 70% degree of methylesterification (DM) at pH 4.5 and 7.0, respectively. Introduced demethylesterified blocks (DMBs) were released by a limited endo-polygalacturonase (EPG) digestion, separated and quantified by HPAEC. Average DMB size ( B S ¯ ) and number of such blocks per molecule ( B N ¯ ) differed depending on final DM and reaction pH ( P < 0.05). B S ¯ and B N ¯ were significantly higher in 30% DM HG than 50 and 70 DMs. pH 4.5 series showed significantly larger B S ¯ compared to pH 7.5 series ( P < 0.01). Distribution of DMBs released by limited EPG digest was predicted by mathematical modeling and in silico modeled processive (degree of processivity = 10), multiple attack mode of action best explains the experimental block distributions. Absolute degree of blockiness (DBabs ) obtained from exhaustive EPG digestions, displayed a linear relationship with DM regardless of reaction pH (P < 0.001). Significant correlation coefficients between B S ¯, B N ¯, DBabs, and DM manifested the effectiveness of the block information gained from both EPG digestion to estimate DMB distribution pattern (P < 0.05). However, comparison of block distribution information of three isozymes revealed that difference in block pattern could be manifested by parameters from limited EPG digest ( B S ¯, B N ¯ ) but not by those from exhaustive digest (DB/DBabs ). The results suggested the possibility to control B S ¯ and to customize specific population of demethylesterified pectin molecules using PME isozymes from Valencia orange. Graphical abstract: Highlights: Pectin methylesterase from citrus was used to demethylesterify a model homogalacturonan. Average demethylesterified block size ( B S ¯ ) and number ( B N ¯ ) differed depending on DM and pH. In silico modeled processive multiple attack mode of action best explained block distributions. Significant correlation between B S ¯, B N ¯, absolute degree of blockiness (DBabs ) and DM was observed. B S ¯ & B N ¯ manifested difference in block distribution among three citrus isozymes but DBabs could not.